2001
DOI: 10.1103/physrevlett.86.5389
|View full text |Cite
|
Sign up to set email alerts
|

Field Cooling Induced Changes in the Antiferromagnetic Structure of NiO Films

Abstract: The magnetic anisotropy in antiferromagnetic 500 A thick NiO films, before and after the establishment of an exchange bias field with Co84Fe16 ferromagnetic layers, was measured using magnetic linear dichroism in soft x-ray absorption. Both <111> textured NiO and untextured NiO films show exchange-bias induced in-plane magnetic anisotropy of nearly equal magnitude and with the Ni moment axis being nearly parallel to the exchange bias field direction. These results represent the first observation of the key ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 23 publications
3
72
0
Order By: Relevance
“…This furnishes an interpretation of the macroscopic behavior of the ferromagnetic layer in terms of the thermally driven evolution of the magnetic state of the antiferromagnet layer. experimentally [1][2][3][4][5][6]. The effect of AFM spins on the EB is difficult to clarify due to the zero net magnetization in the AFM layer [7][8][9][10].…”
mentioning
confidence: 99%
“…This furnishes an interpretation of the macroscopic behavior of the ferromagnetic layer in terms of the thermally driven evolution of the magnetic state of the antiferromagnet layer. experimentally [1][2][3][4][5][6]. The effect of AFM spins on the EB is difficult to clarify due to the zero net magnetization in the AFM layer [7][8][9][10].…”
mentioning
confidence: 99%
“…Many experimental and theoretical studies have shown that the existence of domains in the AF layer is necessary for the appearance of exchange bias in FM/AF bilayers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Theoretical models have suggested both parallel and perpendicular domain walls. Mauri et al 3 suggested that a domain wall forms in the AF layer parallel to the interface while the magnetization of the FM layer rotates.…”
mentioning
confidence: 99%
“…A net AF moment at the interface is necessary for the appearance of both the in-plane and out-of-plane exchange-coupling field. 3,22,23 Field cooling in the presence of a FM layer has been shown to alter the populations of the equivalent AF domains in the NiO layer. 22 Fields parallel to the surface will increase the population of domains with the easy axis parallel to the interface, while an out-of-plane applied field will increase the population of domains with the easy axis perpendicular to the interface.…”
Section: Resultsmentioning
confidence: 99%
“…3,22,23 Field cooling in the presence of a FM layer has been shown to alter the populations of the equivalent AF domains in the NiO layer. 22 Fields parallel to the surface will increase the population of domains with the easy axis parallel to the interface, while an out-of-plane applied field will increase the population of domains with the easy axis perpendicular to the interface. In our as-deposited sample, the field is provided by the FM Ni layer and is directed out-of-plane, leading to a larger population of out-of-plane domains.…”
Section: Resultsmentioning
confidence: 99%